New Kids on the DRDoS Block: Characterizing Multiprotocol and Carpet Bombing Attacks - Heinrich, Tiago; Obelheiro, Rafael R.; Maziero, Carlos A. (Passive and Active Measurement, 2021)
Distributed reflection denial of service (DRDoS) attacks are widespread on the Internet. DRDoS attacks exploit mostly UDP-based protocols to achieve traffic amplification and provide an extra layer of indirection between attackers and their victims, and a single attack can reach hundreds of Gbps. Recent trends in DRDoS include multiprotocol amplification attacks, which exploit several protocols at the same time, and carpet bombing attacks, which target multiple IP addresses in the same subnet instead of a single address, in order to evade detection. Such attacks have been reported in the wild, but have not been discussed in the scientific literature so far. This paper describes the first research on the characterization of both multiprotocol and carpet bombing DRDoS attacks. We developed MP-H, a honeypot that implements nine different protocols commonly used in DRDoS attacks, and used it for data collection. Over a period of 731 days, our honeypot received 1.8 TB of traffic, containing nearly 20.7 billion requests, and was involved in more than 1.4 million DRDoS attacks, including over 13.7 thousand multiprotocol attacks. We describe several features of multiprotocol attacks and compare them to monoprotocol attacks that occurred in the same period, and characterize the carpet bombing attacks seen by our honeypot.